Why has EU macroeconomic governance become more supranational?. Issue 5 (28th July 2016) - Dehousse, Renaud
Abstract: While much of the literature on the Euro crisis has highlighted the intergovernmental features of the European Union response, it appears that in strategic areas, such as macroeconomic policy or banking regulation, supranational institutions have seen their discretionary powers significantly enhanced and that they have played an instrumental role in bringing about such a change. This is all the more remarkable considering the decline in support for integration among governments and the public. This article explains this paradox by the dramatic character of the crisis and the deep mistrust that existed between European states at the time. It also suggests that the process could be hard to reconcile with attempts at 'politicizing' EU public policy.